1962
DOI: 10.2134/agronj1962.00021962005400040026x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Whey on Soil and Plant Growth1

Abstract: Synopsis Whey was effective in increasing corn yields the first and second growing season after application. If, during one season more than 4 acre‐inches of whey are applied sufficient salts may accumulate to temporarily inhibit plant growth. The protein in whey is readily converted to nitrates. Whey also benefited the soil physical status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 1 publication
0
20
0
1
Order By: Relevance
“…Paterson et al [46] reported reduced soil redox potential as a result of high whey application which caused solubilization of Fe and Mn and contamination of domestic drinking water wells. Sharralt et al [47] reported that for each mm (10 3 /ha) of whey applied to the soil, about 400-600 kg of total salt per hectare was added which resulted in high soil salinity and reduced crop yield. Jones et al [48] reported that acid whey can also adversely affect soil pH to the point of it becoming injurious to crops.…”
Section: Nitrogen Losses In Leachatementioning
confidence: 99%
“…Paterson et al [46] reported reduced soil redox potential as a result of high whey application which caused solubilization of Fe and Mn and contamination of domestic drinking water wells. Sharralt et al [47] reported that for each mm (10 3 /ha) of whey applied to the soil, about 400-600 kg of total salt per hectare was added which resulted in high soil salinity and reduced crop yield. Jones et al [48] reported that acid whey can also adversely affect soil pH to the point of it becoming injurious to crops.…”
Section: Nitrogen Losses In Leachatementioning
confidence: 99%
“…While that may occur, problems not related to soil structure would likely arise (Jones et al, 1993). Salts may increase, reaching concentrations toxic to vegetation (Sharratt et al, 1962). Moreover, the soil may become organically overloaded so that suspended solids and/or microbiological growth may clog pores at or near the soil surface, reducing infiltration rates and hydraulic conductivities (McAuliffe et al, 1982).…”
Section: Greenhousementioning
confidence: 99%
“…High whey application rates and/or use of excessively saline irrigation water (EC > 1.2 dS m -1 ) could increase root zone salinity (Jones et al, 1993;Robbins & Lehrsch, 1992;Sharratt et al, 1962). Excessive whey applications could also decrease infiltration rates in the short term due to organic overloading (McAuliffe et al, 1982;Watson et al, 1977) and thus hinder sodium leaching from the profile.…”
mentioning
confidence: 99%
“…High whey application rates could increase root zone salinity , Robbins and Lehrsch 1992, Sharratt et al 1962. Excessive whey applications could also decrease infiltration rates in the short term owing to organic overloading (McAuliffe et al 1982, Watson et al 1977.…”
Section: Introductionmentioning
confidence: 99%